Generation of Terawatt-Scale Vortex Pulses Based on Optical Parametric Chirped-Pulse Amplification - Wangjun Pan; Xiaoyan Liang; Lianghong Yu; Aotian Wang; Jinfeng Li; Ruxin Li (IEEE Photonics Journal, 2020)
In this letter, we report the demonstration of terawatt (TW)-scale femtosecond vortex laser pulses based on noncollinear optical parametric chirped-pulse amplification (OPCPA) centered at 800 nm. To the best of our knowledge, this is the first experimental study of amplification for OPCPA-based vortex pulses to achieve a powerful ultrafast (TW-scale) vortex pulse output. In this experiment, a 0.5-mJ broadband chirped vortex pulse was amplified to 47 mJ with a 15-mm-long LiB3O5 crystal. The double-pass grating pair compressor with an efficiency of 65% maintained the beam vortex, and a pulse of width 30.1 fs was obtained, corresponding to a peak power of 1.02 TW. This laser can be used in studies on nonlinear optics and relativistic laser-plasma interactions, compact plasma-based accelerators, and light sources.